Lyotropic 'hairy' TiO2 nanorods. Issue 1 (17th August 2018) - Cheng, Fei; Verrelli, Emanuele; Alharthi, Fahad A.; Kelly, Stephen M.; O'Neill, Mary; Kemp, Neil T.; Kitney, Stuart P.; Lai, Khue T.; Mehl, Georg H.; Anthopoulos, Thomas
Abstract : Titanium dioxide nanorods coated with phosphonate ligands with photoreactive coumarin in a terminal position were prepared. These nanorods form liquid crystalline solutions at high concentrations. Relatively high dielectric constant thin films were prepared from the solution-processable and photocrosslinkable hybrid inorganic/organic titanium dioxide nanorods. Abstract : We report the synthesis of the first stable, solution-processable and photocrosslinkable hybrid organic/inorganic titanium dioxide nanorods as 'hairy rods' coated with phosphonate ligands with photoreactive coumarin groups located in a terminal position. The relationships between the chemical structure of the diethyl-ω-[(7-oxycoumaryl)- n -alkyl]phosphonate ligands on the ligand exchange rate (LER) and the solubility of the resultant ligand-stabilized titanium dioxide nanorods in organic solvents are elucidated. These TiO2 nanorods, with an organic ligand coating, are short enough (aspect ratio = 5–8) to be dissolved in chlorobenzene at high concentrations, but long enough to form lyotropic nematic liquid crystals. These colloidal solutions are used to deposit a thin, uniform layer of hybrid organic/inorganic TiO2 nanorods with their long axes in the plane of a flat, smooth substrate through a self-organization process. Standard photolithographic patterning creates an insoluble dielectric layer of the desired thickness, smoothness and uniformity and with a dielectric constant of sufficient magnitude, k = 8, suitable for the fabrication of multilayer, plastic electronic devices using solution-based fabrication techniques, such as ink-jet printing, used in roll-to-roll manufacturing.